THE USE OF SMART CLASS APPLICATIONS IN DIGITAL LEARNING IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS - Farhan, Achmad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This research examines the use of the Smart Class application in digital learning in Islamic Religious Education (PAI) subjects at SMP Muhammadiyah 15 Surabaya. Using a qualitative approach and case study method, this research aims to understand how the app affects learning quality and student engagement. Data were obtained through interviews and observations of teachers and students, focusing on the effectiveness and constraints of using the app. The results show that the Smart Class app, which is equipped with features such as animations, E-books and practice questions, has a positive impact on students' learning motivation. Teachers can deliver material in a more interesting and interactive way, although there are some constraints in curriculum suitability. The app has the potential to improve student learning outcomes if implemented effectively with training support for teachers.